ADAMS-PA: Facilitators and Barriers of long-term adherence to physical activity in MS – Results from a German RIMS funded survey study - Riemann-Lorenz, Karin; Coote, Susan; Casey, Blathin; Motl, Robert; Wienert, Julian; Streber, René; Heesen, Christoph (23rd Annual Rims Conference MS Rehabilitation across the lifespan, 2018)
Background: Systematic reviews support the beneficial effects of physical activity (PA) and exercise on various outcomes in Multiple Sclerosis (MS), yet such outcomes require long-term engagement. We examined the facilitators and barriers of long-term adherence with PA and exercise in MS. Methods: We focused on the findings of three behavior change models associated with PA behavior change and a review of the MS-specific literature. We conducted 12 interviews with MS exercise experts from various disciplines and five European countries. We used the Theoretical Domains Framework (TDF) to structure the variety of identified constructs, identified valid scales and developed a comprehensive online survey questionnaire. We collected data from 1529 people with MS (pwMS) in Germany from 19th of April until 4th of October 2017. Results: We classified adherence to regular PA with a modified Physical Activity Staging Questionnaire. Descriptive analysis indicated that 52.8 % of our sample were classified as long-term active (≥ 1y), 12.5% as currently active (≥ 6 months but <1 y) and 34.7 % as not active on a regular basis. Long-term active pwMS had more positive experiences with PA, scored higher on intrinsic motivation, and perceived less environmental barriers compared with the group that was not active (p<0.001). Those classified as not active scored lower on behavioural regulation and worse on measures of depression compared with the long-term active group (p<0.001). Two thirds reported receiving no or not much information about PA and MS, 72% were not aware of PA guidelines and 48% had no knowledge about appropriate athletic exercises or physical activities for pwMS. Perspective: Our comprehensive questionnaire was well accepted and provided important information on determinants of long-term involvement in PA and exercise among pwMS. We are currently analysing the impact of TDF constructs on PA adherence and are preparing surveys in other countries.
Keywords: physical activity; survey; Germany; multiple sclerosis; facilitator; barrier